Pemerolehan Mustholahat Arab pada Anak melalui Media Sosial - Luthfi Arief Sunardi (Pusat Riset dan Inovasi Nasional, 2023)
This research is a study that describes linguistics and science that studies humans and culture as a whole. Researchers review this case through two fields, namely, Psycholinguistics and Anthropolinguistics. The field of Psycholinguistics is the science of language that studies the relationship between psychology and language. Meanwhile, Anthropolinguistics is the study of humankind from its culture and traditions. This study aims to find out how the encouragement of the culture they adhere to, and to find out the process of children aged around 9 to 11 years in obtaining, knowing and learning Mustholahat Arabic through social media, especially on the YouTube platform. Which often displays Arabic-based content in the form of Vlogs, Pranks and the like. While the techniques used to examine this research are listening techniques and interview techniques to the research object. The method used to study this study is a descriptive quantitative method. With this method, it is expected to find patterns formed in these children in obtaining Mustholahat Arabic through social media. And the results of this study will explain how the process of these children obtaining Mustholahat and applying it in everyday life. And also this research will explain the impact of social media for children aged 9 to 11 years in learning Arabic through social media.